Analisis Kinerja Keuangan PT Bank Syariah Indonesia Periode 2021-2022 - M. Yusuf Amar; Selin Jurniasari; Pungki Amelia; Resti Fauziah; Carmidah Carmidah (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2023)
This article discusses the development of sharia banking in Indonesia, with a focus on the financial performance of PT Bank Syariah Indonesia. After experiencing the financial crisis in 1998 and the global crisis in 2008, Islamic banks continued to exist and showed resilience to the impact of the crisis. In 2015, the government plans to merge three state-owned sharia banks to increase efficiency and encourage sharia economic growth. The purpose of this article is to evaluate the financial performance of Bank Syariah Indonesia based on profitability, liquidity and solvency ratios. The research method uses a quantitative descriptive approach with data analysis from Bank Syariah Indonesia's financial reports for the 2021-2022 period. The research results show good financial performance, with profitability, liquidity and solvency ratios entering the good to very good category. This article contributes to understanding the contribution of Islamic banks to the national economy through financial performance evaluation.